Type 1 diabetes susceptibility alleles are associated with distinct alterations in the gut microbiota - Mullaney, Jane A.; Stephens, Juliette E.; Costello, Mary-Ellen; Fong, Cai; Geeling, Brooke E.; Gavin, Patrick G.; Wright, Casey M.; Spector, Timothy D.; Brown, Matthew A.; Hamilton-Williams, Emma E. (Microbiome, 2018)
Dysbiosis of the gut microbiota has been implicated in the pathogenesis of many autoimmune conditions including type 1 diabetes (T1D). It is unknown whether changes in the gut microbiota observed in T1D are due to environmental drivers, genetic risk factors, or both. Here, we have performed an analysis of associations between the gut microbiota and T1D genetic risk using the non-obese diabetic (NOD) mouse model of T1D and the TwinsUK cohort. Through the analysis of five separate colonies of T1D susceptible NOD mice, we identified similarities in NOD microbiome that were independent of animal facility. Introduction of disease protective alleles at the Idd3 and Idd5 loci (IL2, Ctla4, Slc11a1, and Acadl) resulted in significant alterations in the NOD microbiome. Disease-protected strains exhibited a restoration of immune regulatory pathways within the gut which could also be reestablished using IL-2 therapy. Increased T1D disease risk from IL-2 pathway loci in the TwinsUK cohort of human subjects resulted in some similar microbiota changes to those observed in the NOD mouse. These findings demonstrate for the first time that type 1 diabetes-associated genetic variants that restore immune tolerance to islet antigens also result in functional changes in the gut immune system and resultant changes in the microbiota.